2005
DOI: 10.1002/lsm.20181
|View full text |Cite
|
Sign up to set email alerts
|

Results of nonablative wrinkle reduction with a 1,450-nm diode laser: Difficulties in the assessment of “subtle changes”

Abstract: Our study failed to provide convincing data on the efficacy of nonablative treatment of rhytides with the 1,450 nm diode laser. In this respect, we challenge objective judgment in the assessment of subtle changes in nonablative wrinkle reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…The prolonged recovery time and significant risk profile associated with the highly effective ablative techniques prompted the development of nonablative and fractional methods [3, 4]. Nonablative fractional photothermolysis creates thermal damage in the dermis without causing significant epidermal removal or injury.…”
Section: Introductionmentioning
confidence: 99%
“…The prolonged recovery time and significant risk profile associated with the highly effective ablative techniques prompted the development of nonablative and fractional methods [3, 4]. Nonablative fractional photothermolysis creates thermal damage in the dermis without causing significant epidermal removal or injury.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ablative laser surgery using CO 2 or erbium:yttrium aluminium garnet (Er:YAG) laser applied in a conventional manner has been demonstrated to be the most effective option [1][2][3][4]. However, these treatment modalities have been frequently associated with significant downtime, delayed reepithelialization, prolonged erythema, and in some instances resulted in scarring and post-inflammatory hypopigmentation [5][6][7], whereas non-ablative lasers create less side effects [8][9][10][11], and produce limited albeit reasonable efficacy [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies have indicated significant levels of patient satisfaction and even histological and biochemical evidence of improvement, photographic assessment by blinded observers has often found only minimal or no improvement. Thus, limited clinical efficacy is the major disadvantage of this technique compared to ablative laser skin resurfacing [16,17].…”
Section: Discussionmentioning
confidence: 99%